A universidade e as aprendizagens significativas: contribuições possíveis na formação de professores - Felden, Eliane de Lourdes (Universidade do Vale do Rio do Sinos, 2009)
This research aims to investigate the university and a meaningful learning process, hearing from university professors the way they conduct the learning process. The study is divided into three axes: The University and the acquisition of knowledge by Professors, The Professional Knowledge in the Teaching Process and the significant Learning, examined after a deep study of Gimeno Sacristán (1998, 2005, 2007), Cunha (1989, 1998, 1999, 2001, 2006, 2007), Rios (1993, 2006), Pérez Gómez (2001), Tardif(1991, 2000, 2002), Nóvoa (1989, 1990, 1991, 1992, 2008), Freire (1986, 1994, 1996) Pimenta (1999, 2002, 2005), Marcelo García(1999), Schön (1992,2000), Ausubel (1968,1978,2003), Anastasiou (2002, 2007). The research uses data sampling, first educational years, Language graduation courses, Pedagogy, History and Pedagogy offered at the Universidade Regional Integrada do Alto Uruguai e das Missões - URI de Santo Ângelo-RS. The research is based on a qualitative study in which questionnaires were used by undergraduate s
Keywords: aprendizagens significativas; saberes profissionais docentes; formação de professores universitários; background knowledge of teachers; meaningful learning; the teaching process for teachers; Ciências Humanas